(untitled) (Journal of Partial Differential Equations, 1990)
Applying Nash-Moser’s implicit function theorem, the author proves the existence of periodic solution to nonlinear wave equation u_tt - u_xx + &#949g(t, x, u, u_t, u_x, u_tt, u_tx, u_xx) = 0 with a dissipative boundary condition, provided &#949 is sufficiently small.